Downregulated RPS-30 in Angiostrongylus cantonensis L5 plays a defensive role against damage due to oxidative stress - Sun, Wei-Wei (Parasit Vectors, 2020)
BACKGROUND: Eosinophilic meningitis, caused by fifth-stage larvae of the nematode (roundworm) Angiostrongylus cantonensis, is mainly attributed to the contribution of eosinophils to tissue inflammatory responses in helminthic infections. Eosinophils are associated with the killing of helminths via peroxidative oxidation and hydrogen peroxide generated by the dismutation of superoxide produced during respiratory bursts. In contrast, when residing in the host with high level of eosinophils, helminthic worms have evolved to attenuate eosinophil-mediated tissue inflammatory responses for their survival in the hosts. In a previous study we demonstrated that the expression of the A. cantonensis RPS 30 gene (Acan-rps-30) was significantly downregulated in A. cantonensis L5 roundworms residing in cerebrospinal fluid with a high level of eosinophils. Acan-RPS-30 is a protein homologous to the human Fau protein that plays a pro-apoptotic regulatory role and may function in protecting worms from oxidative stress. METHODS: The isolation and structural characterization of Acan-RPS-30 were performed using rapid amplification of cDNA ends (RACE), genome walking and bioinformatics. Quantitative real-time-PCR and microinjection were used to detect the expression patterns of Acan-rps-30. Feeding RNA interference (RNAi) was used to knockdown the apoptosis gene ced-3. Microinjection was performed to construct transgenic worms. An oxidative stress assay was used to determine the functions of Acan-RPS-30. RESULTS: Our results showed that Acan-RPS-30 consisted of 130 amino acids. It was grouped into clade V with C. elegans in the phylogenetic analysis. It was expressed ubiquitously in worms and was downregulated in both L5 larvae and adult A. cantonensis. Worms expressing pCe-rps30::Acan-rps-30::rfp, with the refractile “button-like” apoptotic corpses, were susceptible to oxidative stress. Apoptosis genes ced-3 and ced-4 were both upregulated in the transgenic worms. The phenotype susceptible to oxidative stress could be converted with a ced-3 defective mutation and RNAi. rps-30(−/−) mutant worms were resistant to oxidative stress, with ced-3 and ced-4 both downregulated. The oxidative stress-resistant phenotype could be rescued and inhibited by through the expression of pCe-rps30::Acan-rps-30::rfp in rps-3(−/−) mutant worms. CONCLUSION: In C. elegans worms, downregulated RPS-30 plays a defensive role against damage due to oxidative stress, facilitating worm survival by regulating downregulated ced-3. This observation may indicate the mechanism by which A. cantonensis L5 worms, with downregulated Acan-RPS-30, survive in the central nervous system of humans from the immune response of eosinophils. GRAPHIC ABSTRACT: [Image: see text]